Fretting tests for cyclic plastic law identification: Application to a 1XXX aluminium crossed wire contact. (January 2023) - Arnaud, P.; Maurel, V.; Fouvry, S.; Said, J.; Yang, C.; Hafid, F.
Abstract: To predict the fretting fatigue endurance, it is essential to precisely evaluate the contact size extension to achieve reliable fatigue stress computations. This aspect is widely investigated in the literature regarding surface wear extension induced by gross slip slidings. It can also be critical under partial slip when significant plastic deformations are generated in the interface. A coupled approach involving a 1XXX aluminum crossed wires contact for overhead conductor application is here considered. An original Levenberg-Marquardt strategy for identifying plastic law combining cyclic tensile tests and a set of fretting scars is introduced. This new approach improves by more than 15% the contact size extension prediction of fretting and fretting-fatigue conditions compared to the usual tensile test identification strategy.